2014
DOI: 10.1007/s11255-014-0834-7
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptor immunohistochemistry in genitourinary neoplasms

Abstract: Our data show that the sensitivity of AR immunohistochemistry for prostate cancer is 94.8%. However, the specificity of AR is only 81.4%, among our cohort of invasive genitourinary tumors. Thus, we find the specificity of AR suboptimal, yet AR may remain useful as a component of an immunostain panel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 22 publications
2
26
0
Order By: Relevance
“…12,[14][15][16][17][18][19][20] In accordance with our current findings in UUTUCs, significant decreases in the ARpositive rate have been reported in BCs, compared with nonneoplastic urothelial tissues. [14][15][16] In contrast, 2 other studies showed no AR expression in normal bladder urothelium.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…12,[14][15][16][17][18][19][20] In accordance with our current findings in UUTUCs, significant decreases in the ARpositive rate have been reported in BCs, compared with nonneoplastic urothelial tissues. [14][15][16] In contrast, 2 other studies showed no AR expression in normal bladder urothelium.…”
Section: Discussionsupporting
confidence: 92%
“…6,7 adjacent or separate non-neoplastic urothelial tissue specimens. 9 However, there were only a few studies demonstrating the expression of steroid hormone receptors, such as AR [10][11][12] and ERb, 11 in UUTUCs. In the current study, we aimed to determine the expression status of these 5 steroid hormone receptors in UUTUCs and corresponding non-neoplastic urothelial tissues as well as to assess their correlations with clinicopathological features of the tumors.…”
Section: Introductionmentioning
confidence: 99%
“…90,91 Immunohistochemcal studies found positive AR expression in 12.5-19.0% of primary RCC tumours. 92,93 Shortliffe et al 38 investigated the influence of testosterone on kidney morphometry in juvenile male rats. Rats that were injected with testos terone on a weekly basis had a significantly increased kidney:bodyweight ratio compared with rats in the control groups (P <0.05).…”
Section: Gender Differences In Rccmentioning
confidence: 99%
“…Finally, data were available from five studies on AR expression and bladder cancer susceptibility (568 tumor cases vs. 523 normal controls), six studies on AR expression and tumor grade (387 low grade vs. 663 high grade cases), nine studies on AR expression and tumor stage (582 non-invasive vs. 712 invasive cases), five studies on AR expression and RFS (414 cases) and four studies on AR expression and PFS (319 cases). The essential information of the included studies was listed in Table I ( [8][9][10][11][19][20][21][22][23][24][25][26].…”
Section: Resultsmentioning
confidence: 99%